Co zjada Hamleta? Robaki jako aktywni aktorzy w elsynorskiej (i nie tylko) gastronomii - Sosnowska, Monika (Zoophilologica. Polish Journal of Animal Studies, 2020)
Having been inspired by William Shakespeare’s Hamlet – a drama where both a ghost and a worm find their shelter – the author discusses contacts, interactions relations, and interdependence between human and non-human animals. During the investigation of his father’s “unnatural death,” Hamlet becomes aware of many natural phenomena, including organic cycle (in which worms play a crucial role). Although worms are culturally insignificant, they are significant organisms for ecosystems. As recyclers and fertilizers, they have real impact on ecosystem’s condition and equilibrium. The author exploits contemporary scientific knowledge to identify worms (mentioned in the play) by naming specific invertebrates in accordance with valid taxonomy. To refer to non-human Others, an innovative word – ‘The BioDiverse’ – is proposed. Additionally, Hamlet becomes an inspiration to reflect upon old and new funeral eco-practices, as well as the author’s future funeral – its place and form. The article is written from an ecocritical perspective.